Classification red blood cells using support vector machine - Akrimi J.A.; Suliman A.; George L.E.; Ahmad A.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cells; Classification (of information); Cytology; Diagnosis; Feature extraction; Image processing; Image segmentation; Imaging techniques; Medical imaging; Support vector machines; Classifier algorithms; Clinical diagnosis; Confusion matrices; Image processing technique; Mean Filte; Red blood cell; Retrieval systems; SVM; Blood